The logos of the sensible world : Merleau-Ponty's phenomenological philosophy - Sallis, John, 1938- (Collected writings of John Sallis, 2019)
This volume of the collected writings of John Sallis presents a two-semester lecture course on Maurice Merleau-Ponty given at Duquesne University from 1970 to 1971. Devoted primarily to a close reading of the French philosopher's magnum opus, Phenomenology of Perception, the course begins with a detailed analysis of The Structure of Behavior. The central topics considered in the lectures include the functions of the phenomenological body; beyond realism and idealism; the structures of the lived world; spatiality, temporality, language, sexuality; and perception and knowledge. Sallis illuminates Merleau-Ponty's first two works and offers a thread to follow through developments in his later essays. Merleau-Ponty's notion of the primacy of perception and his claim that "the end of a philosophy is the account of its beginning" are woven throughout the lectures. For Sallis's part, these lectures are foundational for his extended engagement with Merleau-Ponty's The Visible and the Invisible, which was published in Sallis's Phenomenology and the Return to Beginnings